Effects of Preoperative Use of Biologic Agents on Operative Outcomes in Crohn's Disease Patients. Issue 9 (September 2018) - Kamel, Amir Y.; Ayoub, Fares; Banerjee, Debdeep; Chaudhry, Naueen; Ader, Yan; Tan, Sanda; Zimmermann, Ellen M.; Glover, Sarah C.; Iqbal, Atif
Although the effects of biologic agents on postoperative outcomes in Crohn's disease patients have been extensively studied, the effects on intraoperative outcomes, including blood loss, operative time, and length of small bowel resection, remain to be determined. This was a retrospective cohort study at a single tertiary referral center. Crohn's disease (CD) patients who underwent major abdominal surgery were identified. Patients receiving preoperative biologic agents were compared with controls. We compare operative outcomes between groups. A total of 144 patients who underwent major abdominal surgery at the University of Florida between March 2007 and March 2017 were included. One hundred and ten patients (76%) who received pre-operative biologic therapy were compared with 34 controls. On univariate analysis, preoperative biologic use was associated with a significantly shorter length of small bowel resection (21.2 cm in biologic group vs 34.5 cm, P = 0.01). There were no significant differences in intraoperative blood loss (100 vs 87.5 mL, P = 0.40) or total operative time (142 vs 154 minutes, P = 0.39) between groups. On multivariate analysis controlling for variables reflecting severity of disease and malnutrition, biologic use remained significantly associated with shorter length of bowel resection (incident rate ratio 0.58, P = 0.04). Preoperative biologic use is associated with a significantly shorter length of bowel resection in CD patients undergoing major abdominal surgery. No negative effects were noted on operative blood loss or total operative time. Our findings allow improved preoperative planning for surgeons and informed decision-making for CD patients undergoing major abdominal surgery.